The creep behaviour of nickel alloy 718 manufactured by laser powder bed fusion. (June 2021) - Sanchez, S.; Gaspard, G.; Hyde, C.J.; Ashcroft, I.A.; G.A., Ravi; Clare, A.T.
Abstract: Components manufactured by laser powder bed fusion (LPBF) are limited by their performance for use in critical applications. LPBF materials have microstructural defects, such as suboptimal grain size and morphology, and macroscale anomalies, such as lack of fusion. This results in LPBF components performing below their wrought counterparts for various mechanical properties, such as creep which has seldom been researched. To understand the creep behaviour of LPBF alloy 718, parts were fabricated using different scanning strategies and build orientations and creep tested at 650 °C under a 600 MPa load. Heat treatment increased the creep life by a factor of 5, confirming its necessity. The build orientation and stress state were shown to be determining factors in the creep failure mechanisms. The Meander scanning strategy resulted in a 58% increase in creep life compared to the Stripe strategy, due to the detrimental effects of the numerous laser overlapping regions in the Stripe strategy. For a given strategy, a 24% increase in creep life compared to wrought alloy 718 was observed, indicating that LPBF has the potential to surpass wrought material properties. As a result of this work, it is possible to propose build strategies for high temperature creep applications. Graphical abstract: Unlabelled Image Highlights: An additively built specimen obtained a similar creep rate and a 24% longer creep life than wrought alloy 718. The build orientation and stress state of the specimens are responsible for the specimens' different failure modes. The Stripe strategy has numerous laser overlapping areas which cause poorer creep properties than the Meander strategy. δ-precipitates are key for creep performance as they impede microvoid coalescence and slow the creep rate.